Tenaga Nasional Berhad / Nik Muhamad Afiq Rohairul - Rohairul, Nik Muhamad Afiq (Universiti Teknologi MARA, Perlis, 2023)
In completing my bachelor’s degree journey, it is expected to end with internship session on my 6th semester. What needs to be started must come to an end, thus 1 March 2023 is a starting journey my experience at Tenaga Nasional Berhad, (TNB) Kelantan branch. All the journeys consist of my 24 weeks of internship approximately from 1 March 2023 till 15 August 2023 which I have been assigned under Business Support Office (BSO) department and supervise by En Khairul Azuan Bin Ibrahim. As a student, it really gives me exposure to real world working tasks and environment. In this report also, I am observing and trying to identify Tenaga Nasional Berhad (TNB) swot analysis which helpful on individual and company strength, weaknesses, opportunity, and threats. To sum up, my report will reflect the company objective and I will also attach a recommendation. I will also give conclusion regarding internship experience at Tenaga Nasional Berhad (TNB), Kelantan Branch